A low cost 0 decarburization hot rolled steel billet production process

CN117600425BActive Publication Date: 2026-10-27ZENITH STEEL GROUP CORP CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311571086.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-23
Publication Date
2026-10-27
Estimated Expiration
2043-11-23

AI Technical Summary

Technical Problem

对比专利仅通过防脱碳涂料实现两火开坯弹簧钢严脱碳层的控制,其对涂料的制造成本及喷涂成本要求较高

Benefits of technology

[0027]1、本发明利用不同的防脱碳涂料成分、粉料目数及喷涂厚度,控制热轧坯浅脱碳,结合热轧坯单道次浅扒皮,减少了生产成本,同时保证了热轧坯0脱碳的要求;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117600425B_ABST
    Figure CN117600425B_ABST
Patent Text Reader

Abstract

The present application relates to 0 decarburization hot-rolled steel billet production technical field, especially to a kind of low-cost 0 decarburization hot-rolled steel billet production process.The process flow of the present application includes: continuous casting billet-coating anti-decarburization coating-breaking down-hot rolled billet finishing (light scalping)-hot rolled billet rolling, by studying the ingredient of anti-decarburization coating, powder mesh and spraying thickness, control the decarburization depth of hot-rolled billet is shallow, use the one pass scalping of hot-rolled billet finishing to remove shallow decarburization layer, achieve the requirement of low-cost production 0 decarburization hot-rolled billet.The present application scheme is more conventional only rely on hot-rolled billet deep scalping or only coating anti-decarburization coating process, solve the problem of high production cost.It is suitable for low-cost production 0 decarburization hot-rolled billet, more conventional process cost reduction is more than 50 yuan / ton steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of billet production technology, and in particular to a low-cost, zero-decarburization hot-rolled steel billet production process. Background Technology

[0002] For steel grades requiring severe decarburization and necessitating billet rolling, a prerequisite is the availability of 0% decarburized hot-rolled billets. The conventional method for producing 0% decarburized hot-rolled billets is "continuous casting billet - billet preparation - hot-rolled billet finishing (deep peeling) - hot-rolled billet rolling." This method, due to direct billet rolling, results in a deeper decarburized layer and peeling depth in the hot-rolled billet, leading to increased metal loss, reduced product yield, and increased production costs. Another method is "continuous casting billet - applying anti-decarburization coating - billet preparation - hot-rolled billet rolling." This method eliminates the hot-rolled billet finishing and peeling process, but relies solely on applying anti-decarburization coating to achieve 0% decarburized hot-rolled billets, placing high demands on the manufacturing and application of the anti-decarburization coating, resulting in higher production costs. Therefore, how to produce 0% decarburized hot-rolled billets at low cost has become crucial for enhancing a company's product competitiveness.

[0003] Practical experience has shown that different composition ratios, powder mesh sizes, and spray thicknesses of anti-decarburization coatings significantly affect the decarburization depth of hot-rolled billets. Conventional anti-decarburization coatings contain a wide variety of main element types and contents; powder mesh sizes range from 100 to 500 mesh; and spray thicknesses range from 0.1 mm to 5 mm. Different combinations of these three factors have a significant impact on controlling the decarburization depth of hot-rolled billets. It is generally believed that with a fixed coating composition, a higher proportion of large-mesh powder and a thicker spray thickness result in a shallower decarburization depth, but also higher costs. Based on the above discussion, it is difficult to obtain the optimal combination of low-cost shallow decarburization and shallow peeling processes for hot-rolled billets.

[0004] Patent CN202010438416.7, "Anti-decarburization Protective Coating for Spring Steel Billets During Heating and Its Application," discloses an anti-decarburization protective coating for spring steel billets during heating. The coating provided by this invention is suitable for preventing decarburization during the heating process of spring steel billets before billet preparation and hot rolling. The coating can be directly sprayed onto the surface of the billet below 800℃, with a protection temperature range of 950℃ to 1250℃ and a protection life of 1 to 25 hours. It can effectively slow down the decarburization of the surface of spring steel during high-temperature heating. In contrast, the patent only uses an anti-decarburization coating to control the severe decarburization layer of spring steel billets prepared in two heating processes, which places higher demands on the manufacturing and spraying costs of the coating.

[0005] Patent "CN202210958310.9 Spring Steel Wire and its Production Method" controls the decarburization depth of the hot-rolled billet by controlling the furnace time to 190-220 minutes and the temperature of the continuously cast billet in the furnace to ≤1050℃. The furnace atmosphere composition, by volume percentage, has H2O content ≤1% and O2 content ≤0.5%. The entire surface of the billet is then fully ground with a grinding wheel, with the edge grinding amount controlled to ≥1.0mm and the corner grinding amount controlled to ≥1.2mm. In contrast, the patent controls the decarburization depth of the hot-rolled billet by controlling the furnace temperature, atmosphere, and time, and then controls the decarburization through surface peeling. This method involves a deeper peeling depth (higher cost) and a significantly different decarburization control method compared to this patent. Summary of the Invention

[0006] To address the shortcomings of existing methods, this invention optimizes the cost of the "continuous casting billet - anti-decarburization coating - billet opening - hot-rolled billet finishing - hot-rolled billet rolling" process. By combining the anti-decarburization coating composition, powder mesh size, spraying thickness, and a single-pass shallow peeling process, the requirement of zero decarburization in hot-rolled billets can be met. By tracking the optimization of the anti-decarburization coating composition, powder mesh size, and spraying thickness, combined with hot-rolled billet finishing (shallow peeling), the requirement of zero decarburization in hot-rolled billets can ultimately be achieved. This solution, by optimizing the coating and spraying thickness combined with a single-pass shallow peeling process, reduces overall production costs compared to traditional techniques that only peel hot-rolled billets or only apply anti-decarburization coating to continuous casting billets. Furthermore, based on the optimization of the anti-decarburization coating, spraying thickness, and single-pass shallow peeling, the requirement of zero decarburization in hot-rolled billets is guaranteed. It is suitable for steel grades requiring low-cost production of zero-decarburized billets.

[0007] The technical solution adopted in this invention is: a low-cost, zero-decarburization hot-rolled steel billet production process, including the following steps: continuous casting billet - coating with anti-decarburization coating - billet opening - hot-rolled billet finishing (shallow peeling) - hot-rolled billet rolling.

[0008] Furthermore, the mass percentages of each component in the anti-decarburization coating are as follows: quartz sand (SiO2 purity ≥ 85%): 55%–65%, silicon carbide (SiC purity ≥ 90%): 5%–8%, corundum (Al2O3 purity ≥ 98%): 10%–15%, zirconium corundum (A6Z4 purity ≥ 85%): 5%–8%, chromium oxide (Cr2O3 purity ≥ 95%): 1%–3%, zirconium silicide (ZrSi2 purity ≥ 95%): 1%–2%, barium borate (4B2O3-BaO purity ≥ 95%): 1%–2%, and the remainder is phenolic resin as a binder.

[0009] Among them, the proportion of quartz sand, silicon carbide, corundum, zirconium corundum, chromium oxide, zirconium silicide, and barium boroate with a particle size ≥200 mesh is 55% to 65%.

[0010] Furthermore, the coating thickness of the anti-decarburization coating is 0.25mm to 0.35mm.

[0011] Furthermore, the billet-making process includes heating and rolling of the continuously cast billet, wherein the heating process includes a preheating section, a second preheating section, a first heating section, a second heating section, a soaking section, and initial rolling; the temperature of the preheating section is ≤700℃, the temperature of the second preheating section is 900℃~1050℃, the temperature of the first heating section is 1180℃~1250℃, the temperature of the second heating section is 1210℃~1250℃, the temperature of the soaking section is 1210℃~1250℃, and the initial rolling temperature is 1050℃~1160℃.

[0012] Furthermore, the finishing process involves: performing a single-pass stripping process on the continuously cast billet after the initial billet preparation; the single-pass stripping depth is approximately 0.6 mm.

[0013] Furthermore, the rolling process includes heating and rolling of the hot-rolled billet; wherein, the hot-rolled billet heating process includes heating section 1, heating section 2, soaking section, and initial rolling; the temperature of heating section 1 is 700℃~760℃, the temperature of heating section 2 is 930℃~980℃, the temperature of soaking section is 1050℃~1100℃, and the initial rolling temperature is 940℃~1000℃.

[0014] The production process involves continuous casting billet – applying anti-decarburization coating – billet opening – hot-rolled billet finishing (shallow peeling) – hot-rolled billet rolling. The reason for this is that without applying anti-decarburization coating during billet opening and rolling, the decarburized layer on the hot-rolled billet is deeper, requiring a deeper peeling depth, leading to increased metal loss, reduced product yield, and increased production costs. However, relying solely on anti-decarburization coating to achieve zero-decarburization hot-rolled billets places high demands on the manufacturing and application of the anti-decarburization coating, resulting in high production costs. Therefore, it is necessary to optimize the anti-decarburization coating and control the coating thickness to achieve shallow decarburization of the hot-rolled billet, and then use hot-rolled billet finishing (single-pass shallow peeling) to remove the decarburized layer, ultimately obtaining a zero-decarburized hot-rolled billet.

[0015] The requirement for an anti-decarburization coating composition of 55%–65% quartz sand (SiO2 purity ≥ 85%) is based on the fact that SiO2, as a major component of the anti-decarburization coating, plays a supporting role in the overall powder, ensuring that the coating maintains a certain shape and viscosity after heating. Too low a content will not provide sufficient support, while too high a content will result in excessive viscosity, making it prone to breakage and failing to achieve the desired anti-decarburization effect.

[0016] The requirement for an anti-decarburization coating composition of 5%–8% silicon carbide (SiC purity ≥ 90%) is based on the fact that SiC, as an antioxidant, can resist the oxidation of oxygen in the combustion atmosphere of the heating furnace, reducing the overall oxidation and burn-off of the coating layer. Too low a content will not provide antioxidant effects, while too high a content will cause the coating layer to easily blister, which is detrimental to preventing decarburization.

[0017] The requirement for an anti-decarburization coating composition of 10%–15% corundum (Al2O3 purity ≥ 98%) is based on the fact that Al2O3 can increase the melting point of the coating to a certain extent, ensuring it retains a certain non-liquefied state under high-temperature conditions. It also promotes the descaling effect of high-pressure water during the subsequent blanking process. Too low a content will not raise the melting point, while too high a content will result in an excessively high melting point, which is detrimental to preventing decarburization.

[0018] The requirement for an anti-decarburization coating composition of 5%–8% zirconium corundum (A6Z4 purity ≥ 85%) is due to the fact that adding a certain amount of zirconium corundum can improve the thermal stability of the coating, ensuring that it does not crack at high temperatures. Too low a content will not provide thermal shock resistance, while too high a content will increase the melting point, which is detrimental to preventing decarburization.

[0019] The requirement for an anti-decarburization coating composition of 1% to 3% chromium oxide (Cr2O3 purity ≥ 95%) is because Cr2O3 can adjust the viscosity of the anti-decarburization coating to a certain extent, ensuring a certain covering effect. Too low a content will not have an adjusting effect, while too high a content will lead to excessive viscosity, which is detrimental to anti-decarburization.

[0020] The requirement for an anti-decarburization coating composition of 1%–2% zirconium silicide (ZrSi2 purity ≥ 95%) is due to the fact that ZrSi2 possesses antioxidant capabilities, resisting the oxidation of oxygen in the combustion atmosphere of the heating furnace and reducing the overall oxidation and burn-off of the coating layer. Furthermore, after oxidation, it forms ZrSiO4, whose volume expansion fills voids on the coating surface, improving the anti-decarburization effect. Too low a content results in an insignificant effect, while too high a content leads to excessively high coating viscosity, making it prone to localized shrinkage and breakage.

[0021] The requirement for an anti-decarburization coating composition of 1% to 2% barium borate (4B₂O₃-BaO purity ≥ 95%) is due to the fact that 4B₂O₃-BaO helps stabilize the coating's high-temperature stability, ensures its shape stability, and improves the coating's anti-decarburization effect. Too low a content will result in an insignificant effect, while too high a content will lead to localized shrinkage and damage to the coating.

[0022] The reason for requiring the anti-decarburization coating to consist of a binder of phenolic resin is that phenolic resin is needed to mix various powders to facilitate subsequent high-temperature spraying and bonding to cover the surface of the cast billet.

[0023] The requirement that 55%–65% of the main components (quartz sand, silicon carbide, corundum, zirconium corundum, chromium oxide, zirconium silicide, and barium borophosphate) have a particle size ≥200 mesh is based on the fact that a higher mesh size results in better overall coverage of the cast billet surface after spraying, which is more conducive to improving the decarburization prevention effect, but the cost will also increase accordingly. If the proportion of ≥200 mesh is <55%, the decarburization prevention effect is not obvious, the decarburization depth increases, and the subsequent peeling depth also needs to be increased, increasing the peeling cost; if the proportion of ≥200 mesh is >65%, the decarburization prevention effect increases, but the manufacturing cost also increases accordingly, which is not conducive to cost control.

[0024] The requirement for a coating thickness of 0.25mm to 0.35mm is based on the fact that a thicker coating theoretically provides better control over the decarburized layer and improves the anti-decarburization effect, but also increases the cost. A coating thickness <0.25mm results in poor anti-decarburization, and the increased decarburization depth leads to increased subsequent peeling depth and higher peeling costs. A coating thickness >0.35mm results in a shallower decarburization depth, but also increases spraying costs.

[0025] The requirement for single-pass billet peeling after the initial rolling process, with a peeling depth of approximately 0.6mm, stems from the fact that the grinding depth removed by a single pass of the grinding wheel is approximately 0.6mm. Combined with the control of a shallow decarburized layer using anti-decarburization coatings, this allows for low-cost production. If the peeling depth is too shallow, a single pass will not completely remove the shallow decarburized layer, necessitating a second peeling and increasing costs. Conversely, if the peeling depth is too deep, the direct losses from peeling will be excessive, also leading to increased costs.

[0026] The beneficial effects of this invention are:

[0027] 1. This invention utilizes different anti-decarburization coating components, powder mesh size and spraying thickness to control shallow decarburization of hot-rolled billets. Combined with single-pass shallow peeling of hot-rolled billets, it reduces production costs while ensuring the requirement of 0 decarburization of hot-rolled billets.

[0028] 2. This invention reduces costs by more than 50 yuan per ton of steel compared to conventional processes. Attached image description:

[0029] Figure 1 A schematic diagram of the processing flow of this invention;

[0030] Figure 2 Cost comparison chart of embodiments and comparative examples of the present invention. Detailed Implementation

[0031] The present invention will be further described below with reference to the accompanying drawings and embodiments. The drawings are simplified schematic diagrams, which only illustrate the basic structure of the present invention in a schematic manner, and therefore only show the components related to the present invention.

[0032] like Figure 1As shown, a low-cost, zero-decarburization hot-rolled steel billet production process includes the following steps:

[0033] (1) Apply anti-decarburization coating to the continuous casting billet;

[0034] The continuously cast billet is a 60Si2MnA steel billet with a cross-section of 300*325. The mass percentage range of each component of 60Si2MnA is as follows: C: 0.56%~0.64%, Si: 1.5%~2.0%, Mn: 0.7%~1.0%, P: ≤0.025%, S: ≤0.030%, Cr: ≤0.35%, with the remainder being Fe and unavoidable impurities.

[0035] Among them, the anti-decarburization coatings include ZT001, ZT002, ZT003, ZT004, and ZT005:

[0036] ZT001 comprises the following components in the following mass ratios: quartz sand (SiO2 purity ≥ 85%): 61%, silicon carbide (SiC purity ≥ 90%): 7%, corundum (Al2O3 purity ≥ 98%): 13%, zirconium corundum (A6Z4 purity ≥ 85%): 7%, chromium oxide (Cr2O3 purity ≥ 95%): 2%, zirconium silicide (ZrSi2 purity ≥ 95%): 1.5%, barium borate (4B2O3-BaO purity ≥ 95%): 1.5%, and the remainder is phenolic resin as a binder.

[0037] ZT002 comprises the following components in the following mass ratio (excluding zirconium silicide and barium borate): Quartz sand (SiO2 purity ≥ 85%): 61%, Silicon carbide (SiC purity ≥ 90%): 7%, Corundum (Al2O3 purity ≥ 98%): 13%, Zirconium corundum (A6Z4 purity ≥ 85%): 7%, Chromium oxide (Cr2O3 purity ≥ 95%): 2%, Zirconium silicide (ZrSi2 purity ≥ 95%): 0%, Barium borate (4B2O3-BaO purity ≥ 95%): 0%, with the remainder being phenolic resin as a binder.

[0038] ZT003 comprises the following components in the following mass ratio (zirconium silicide and barium borate content is higher than 6%): quartz sand (SiO2 purity ≥ 85%): 61%, silicon carbide (SiC purity ≥ 90%): 7%, corundum (Al2O3 purity ≥ 98%): 13%, zirconium corundum (A6Z4 purity ≥ 85%): 7%, chromium oxide (Cr2O3 purity ≥ 95%): 2%, zirconium silicide (ZrSi2 purity ≥ 95%): 6%, barium borate (4B2O3-BaO purity ≥ 95%): 6%, with the remainder being phenolic resin as a binder.

[0039] ZT004 comprises the following components in the following mass ratio (zirconium silicide content 0%): quartz sand (SiO2 purity ≥ 85%): 61%, silicon carbide (SiC purity ≥ 90%): 7%, corundum (Al2O3 purity ≥ 98%): 13%, zirconium corundum (A6Z4 purity ≥ 85%): 7%, chromium oxide (Cr2O3 purity ≥ 95%): 2%, zirconium silicide (ZrSi2 purity ≥ 95%): 0%, barium borate (4B2O3-BaO purity ≥ 95%): 1.5%, with the remainder being phenolic resin as a binder.

[0040] ZT005 comprises the following components in the following mass ratio (0% barium borate content): Quartz sand (SiO2 purity ≥ 85%): 61%, Silicon carbide (SiC purity ≥ 90%): 7%, Corundum (Al2O3 purity ≥ 98%): 13%, Zirconium corundum (A6Z4 purity ≥ 85%): 7%, Chromium oxide (Cr2O3 purity ≥ 95%): 2%, Zirconium silicide (ZrSi2 purity ≥ 95%): 1.5%, Barium borate (4B2O3-BaO purity ≥ 95%): 0%, with the remainder being phenolic resin as a binder.

[0041] The main components described in the examples and comparative examples include quartz sand, silicon carbide, corundum, zirconium corundum, chromium oxide, zirconium silicide, and barium borate. The proportions of the main components with a particle size ≥200 mesh are 0%, 10%, 20%, 30%, 50%, 60%, 70%, and 100%, respectively.

[0042] The coating thicknesses are 0.3mm, 0.6mm, 0.9mm, and 1.2mm, respectively.

[0043] (2) The continuous casting billet is rolled into a billet. The billet rolling process is as follows: preheating section, preheating section 2, heating section 1, heating section 2, soaking section, rolling, and seven-section rolling to produce a 160*160 hot-rolled square billet.

[0044] The preheating section temperature is ≤700℃, the second preheating section temperature is 900℃~1050℃, the first heating section temperature is 1180℃~1250℃, the second heating section temperature is 1210℃~1250℃, the soaking section temperature is 1210℃~1250℃, and the initial rolling temperature is 1050℃~1160℃.

[0045] (4) Finish the hot-rolled billet according to the decarburization layer depth, with a single pass removing 0.6 mm (if finishing is required).

[0046] (5) Detection of decarburized layer in hot-rolled billet.

[0047] (6) Hot-rolled billet rolling, the rolling process is: heating section 1, heating section 2, soaking section, rolling start, rolling 20 times to obtain a finished product with φ16mm;

[0048] The heating section 1 has a temperature of 700℃~760℃, the heating section 2 has a temperature of 930℃~980℃, the soaking section has a temperature of 1050℃~1100℃, and the initial rolling temperature is 940℃~1000℃.

[0049] Example 1:

[0050] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 60% and the coating thickness being 0.3mm.

[0051] Then the hot-rolled billet is subjected to roughing rolling.

[0052] The hot-rolled billet is subjected to a single-pass 0.6mm peeling finishing process (the decarburization depth of the hot-rolled billet is 0.54mm).

[0053] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0054] Comparative Example 1: (No anti-decarburization coating applied, only deep peeling of hot-rolled billet)

[0055] No coating is applied to the surface of the 60Si2MnA continuous casting billet.

[0056] The hot-rolled billet is subjected to initial rolling.

[0057] The hot-rolled billet is subjected to 5 passes of 3.0mm peeling finishing (the decarburization depth of the hot-rolled billet is 2.49mm).

[0058] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0059] Comparative Example 2: (Coating applied only, no hot-rolled billet finishing)

[0060] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component being ≥200 mesh accounting for 100% and the coating thickness being 0.3mm.

[0061] The hot-rolled billet is subjected to initial rolling.

[0062] No peeling or finishing is performed on the hot-rolled billet.

[0063] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0064] Comparative Example 3: (ZT002 + 60% mesh size + 0.3mm)

[0065] ZT002 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 60% and the coating thickness being 0.3mm.

[0066] The hot-rolled billet is subjected to initial rolling.

[0067] The hot-rolled billet is subjected to two passes of 1.2mm peeling finishing (the decarburization depth of the hot-rolled billet is 1.13mm).

[0068] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0069] Comparative Example 4: (ZT001 + 50% mesh size + 0.3mm)

[0070] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 50% and the coating thickness being 0.3mm.

[0071] The hot-rolled billet is subjected to initial rolling.

[0072] The hot-rolled billet is subjected to two passes of 1.2mm peeling finishing (the decarburization depth of the hot-rolled billet is 0.82mm).

[0073] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0074] Comparative Example 5: (ZT001 + 70% mesh size + 0.3mm)

[0075] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with 70% of the main component being ≥200 mesh and a coating thickness of 0.3 mm.

[0076] The hot-rolled billet is subjected to initial rolling.

[0077] The hot-rolled billet is subjected to a single-pass 0.6mm peeling finishing process (the decarburization depth of the hot-rolled billet is 0.33mm).

[0078] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0079] Comparative Example 6: (ZT001 + mesh count 0% + 0.6mm)

[0080] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 0% and the coating thickness being 0.6mm.

[0081] The hot-rolled billet is subjected to initial rolling.

[0082] The hot-rolled billet is subjected to four passes of 2.4mm peeling finishing (the decarburization depth of the hot-rolled billet is 2mm).

[0083] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0084] Comparative Example 7: (ZT001 + 10% mesh size + 0.6mm)

[0085] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 10% and the coating thickness being 0.6mm.

[0086] The hot-rolled billet is subjected to initial rolling.

[0087] The hot-rolled billet is subjected to three passes of 1.8mm peeling finishing (the decarburization depth of the hot-rolled billet is 1.73mm).

[0088] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0089] Comparative Example 8: (ZT001 + 20% mesh size + 0.6mm)

[0090] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 20% and the coating thickness being 0.6mm.

[0091] The hot-rolled billet is subjected to initial rolling.

[0092] The hot-rolled billet is subjected to three passes of 1.8mm peeling finishing (the decarburization depth of the hot-rolled billet is 1.54mm).

[0093] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0094] Comparative Example 9: (ZT001 + mesh count 0% + 0.9mm)

[0095] ZT001 coating was sprayed onto the surface of 60Si2MnA continuous casting billet, with the main component ≥200 mesh accounting for 0% and the coating thickness being 0.9mm.

[0096] The hot-rolled billet is subjected to initial rolling.

[0097] The hot-rolled billet is subjected to four passes of 2.4mm peeling finishing (the decarburization depth of the hot-rolled billet is 1.87mm).

[0098] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0099] Comparative Example 10: (ZT001 + 10% mesh size + 0.9mm)

[0100] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 10% and the coating thickness being 0.9mm.

[0101] The hot-rolled billet is subjected to initial rolling.

[0102] The hot-rolled billet is subjected to three passes of 1.8mm peeling finishing (the decarburization depth of the hot-rolled billet is 1.46mm).

[0103] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0104] Comparative Example 11: (ZT001 + 20% mesh size + 0.9mm)

[0105] ZT001 coating was sprayed onto the surface of 60Si2MnA continuous casting billet, with the main component ≥200 mesh accounting for 20% and the coating thickness being 0.9mm.

[0106] The hot-rolled billet is subjected to initial rolling.

[0107] The hot-rolled billet is subjected to three passes of 1.8mm peeling finishing (the decarburization depth of the hot-rolled billet is 1.22mm).

[0108] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0109] Comparative Example 12: (ZT001 + 30% mesh size + 0.9mm)

[0110] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 30% and the coating thickness being 0.9mm.

[0111] The hot-rolled billet is subjected to initial rolling.

[0112] The hot-rolled billet is subjected to two passes of 1.2mm peeling finishing (the decarburization depth of the hot-rolled billet is 0.96mm).

[0113] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0114] Comparative Example 13: (ZT001 + mesh count 0% + 1.2mm)

[0115] ZT001 coating was sprayed onto the surface of 60Si2MnA continuous casting billet, with the main component ≥200 mesh accounting for 0% and the coating thickness being 1.2mm.

[0116] The hot-rolled billet is subjected to initial rolling.

[0117] The hot-rolled billet is subjected to three passes of 1.8mm peeling finishing (the decarburization depth of the hot-rolled billet is 1.6mm).

[0118] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0119] Comparative Example 14: (ZT001 + 10% mesh size + 1.2mm)

[0120] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 10% and the coating thickness being 1.2mm.

[0121] The hot-rolled billet is subjected to initial rolling.

[0122] The hot-rolled billet is subjected to three passes of 1.8mm peeling finishing (the decarburization depth of the hot-rolled billet is 1.21mm).

[0123] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0124] Comparative Example 15: (ZT001 + 20% mesh size + 1.2mm)

[0125] ZT001 coating was sprayed onto the surface of 60Si2MnA continuous casting billet, with the main component ≥200 mesh accounting for 20% and the coating thickness being 1.2mm.

[0126] The hot-rolled billet is subjected to initial rolling.

[0127] The hot-rolled billet is subjected to two passes of 1.2mm peeling finishing (the decarburization depth of the hot-rolled billet is 0.92mm).

[0128] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0129] Comparative Example 16: (ZT001 + 30% mesh size + 1.2mm)

[0130] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 30% and the coating thickness being 1.2mm.

[0131] The hot-rolled billet is subjected to initial rolling.

[0132] The hot-rolled billet is subjected to a 0.6mm peeling finishing process in one pass (the decarburization depth of the hot-rolled billet is 0.58mm).

[0133] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0134] Comparative Example 17: (ZT001 + 50% mesh size + 0.3mm)

[0135] ZT001 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 50% and the coating thickness being 0.3mm.

[0136] The hot-rolled billet is subjected to initial rolling.

[0137] The hot-rolled billet is subjected to a 0.6mm peeling finishing process in one pass (the decarburization depth of the hot-rolled billet is 0.81mm).

[0138] The depth of the decarburized layer in the hot-rolled billet was tested (the decarburized depth of the hot-rolled billet was 0.21 mm, which does not meet the requirement of 0 decarburized hot-rolled billet).

[0139] Comparative Example 18: (ZT003 + 60% mesh size + 0.3mm)

[0140] ZT003 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with the main component ≥200 mesh accounting for 60% and the coating thickness being 0.3mm.

[0141] The hot-rolled billet is subjected to initial rolling.

[0142] The hot-rolled billet is subjected to three passes of 1.2mm peeling finishing (the decarburization depth of the hot-rolled billet is 1.43mm).

[0143] Detecting the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0144] Comparative Example 19: (ZT004 + 60% mesh size + 0.3mm)

[0145] ZT004 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with 60% of the main component being ≥200 mesh and a coating thickness of 0.3mm.

[0146] The hot-rolled billet is subjected to initial rolling.

[0147] The hot-rolled billet is subjected to two passes of 1.2mm peeling finishing (the decarburization depth of the hot-rolled billet is 0.79mm).

[0148] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0149] Comparative Example 20: (ZT005 + 60% mesh size + 0.3mm)

[0150] ZT005 coating was sprayed onto the surface of 60Si2MnA continuously cast billets, with 60% of the main component being ≥200 mesh and a coating thickness of 0.3mm.

[0151] The hot-rolled billet is subjected to initial rolling.

[0152] The hot-rolled billet is subjected to two passes of 1.2mm peeling finishing (the decarburization depth of the hot-rolled billet is 0.83mm).

[0153] Detect the decarburization layer depth of hot-rolled billets (decarburization depth of hot-rolled billets is 0).

[0154] Cost Analysis

[0155] Example 1: ZT001 coating was used, with 60% of the main component being ≥200 mesh, a coating thickness of 0.3 mm, and a cost of 45 yuan / ton of steel; the steel billet was peeled off at a thickness of 0.6 mm, with a single pass, costing 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 45 + 25 = 70 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0156] Comparative Example 1: No coating is used, and the coating cost is 0 yuan / ton of steel; the steel billet is peeled 0.6mm, with 5 peeling passes, costing 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 0 + 25 * 5 = 125 yuan / ton of steel.

[0157] Comparative Example 2: ZT001 coating was used, with 100% of the main component being ≥200 mesh, and a coating thickness of 0.3 mm. The cost was 122 yuan / ton of steel. The steel billet was peeled by 0 mm, with a cost of 0 yuan / ton of steel. Total cost = coating cost + peeling cost = 122 + 0 = 122 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0158] Comparative Example 3: ZT002 coating was used, with 60% of the main component being ≥200 mesh, a coating thickness of 0.3 mm, and a cost of 40 yuan / ton of steel; the steel billet underwent 0.6 mm of peeling, with two passes, costing 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 40 + 25 * 2 = 90 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0159] Comparative Example 4: ZT001 coating was used, with 50% of the main component being ≥200 mesh, a coating thickness of 0.3 mm, and a cost of 37 yuan / ton of steel; the steel billet underwent 0.6 mm of peeling, repeated twice, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 37 + 25 * 2 = 87 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0160] Comparative Example 5: ZT001 coating was used, with 70% of the main component being ≥200 mesh, and a coating thickness of 0.3 mm, costing 55 yuan / ton of steel; the steel billet underwent 0.6 mm of peeling, with one pass, costing 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 55 + 25 = 80 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0161] Comparative Example 6: ZT001 coating was used, with 0% of the main component being ≥200 mesh, and a coating thickness of 0.6 mm. The cost was 2 yuan / ton of steel per 0.3 mm thickness. The steel billet underwent 0.6 mm of peeling, repeated 4 times, costing 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 2*2 + 25*4 = 104 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0162] Comparative Example 7: ZT001 coating was used, with a main component ≥200 mesh comprising 10% of the coating. The coating thickness was 0.6 mm, and the cost was 5 yuan / ton of steel per 0.3 mm thickness. The steel billet underwent 0.6 mm of peeling, repeated 3 times, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 5 * 2 + 25 * 3 = 85 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0163] Comparative Example 8: ZT001 coating was used, with a main component of ≥200 mesh accounting for 20% of the total. The coating thickness was 0.6 mm, and the cost was 10 yuan / ton of steel per 0.3 mm thickness. The steel billet underwent 0.6 mm of peeling, repeated 3 times, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 10 * 2 + 25 * 3 = 95 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0164] Comparative Example 9: ZT001 coating was used, with 0% of the main component being ≥200 mesh, and a coating thickness of 0.9 mm. The cost was 2 yuan / ton of steel per 0.3 mm thickness. The steel billet underwent 0.6 mm of peeling, repeated 4 times, costing 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 2*3 + 25*4 = 106 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0165] Comparative Example 10: ZT001 coating was used, with a main component of ≥200 mesh at a ratio of 10%, and a coating thickness of 0.9 mm. The cost was 5 yuan / ton of steel per 0.3 mm thickness. The steel billet underwent 0.6 mm of peeling, repeated 3 times, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 5 * 3 + 25 * 3 = 90 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0166] Comparative Example 11: ZT001 coating was used, with a main component of ≥200 mesh accounting for 20% of the total. The coating thickness was 0.9 mm, and the cost was 10 yuan / ton of steel per 0.3 mm thickness. The steel billet underwent 0.6 mm of peeling, repeated 3 times, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 10 * 3 + 25 * 3 = 105 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0167] Comparative Example 12: ZT001 coating was used, with a main component of ≥200 mesh accounting for 30% of the coating. The coating thickness was 0.9 mm, and the cost was 17 yuan / ton of steel per 0.3 mm thickness. The steel billet underwent 0.6 mm of peeling, repeated twice, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 17 * 3 + 25 * 2 = 101 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0168] Comparative Example 13: ZT001 coating was used, with a main component ≥200 mesh ratio of 0%, a coating thickness of 1.2 mm, and a cost of 2 yuan / ton of steel per 0.3 mm thickness; the steel billet underwent 0.6 mm of peeling, with 3 peeling passes, costing 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 2*4 + 25*3 = 83 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0169] Comparative Example 14: ZT001 coating was used, with a main component of ≥200 mesh at 10% concentration, and a coating thickness of 1.2 mm. The cost was 5 yuan / ton of steel per 0.3 mm thickness. 0.6 mm of steel billet was peeled off, in 3 passes, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 5 * 4 + 25 * 3 = 95 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0170] Comparative Example 15: ZT001 coating was used, with a main component of ≥200 mesh accounting for 20% of the total. The coating thickness was 1.2 mm, and the cost was 10 yuan / ton of steel per 0.3 mm thickness. The steel billet underwent 0.6 mm of peeling, repeated twice, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 10 * 4 + 25 * 2 = 90 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0171] Comparative Example 16 uses ZT001 coating with a main component of ≥200 mesh at 30% concentration and a coating thickness of 1.2 mm. The cost is 17 yuan / ton of steel per 0.3 mm thickness. The steel billet is peeled 0.6 mm in diameter, requiring one pass, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 17 * 4 + 25 = 93 yuan / ton of steel (decarburization depth of hot-rolled billet is 0).

[0172] Comparative Example 17 uses ZT001 coating with a main component of ≥200 mesh at 50% concentration, a coating thickness of 0.3 mm, and a cost of 37 yuan / ton of steel. The steel billet is peeled 0.6 mm thick in one pass, costing 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 37 + 25 = 62 yuan / ton of steel. The decarburization depth of the hot-rolled billet is 0.21 mm, which does not meet the requirement of 0% decarburization for hot-rolled billets.

[0173] Comparative Example 18: ZT003 coating was used, with 60% of the main component being ≥200 mesh, a coating thickness of 0.3 mm, and a cost of 53 yuan / ton of steel; the steel billet underwent 0.6 mm of peeling, with 3 passes, costing 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 53 + 25 * 3 = 128 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0174] Comparative Example 19: ZT004 coating was used, with 60% of the main component being ≥200 mesh, a coating thickness of 0.3 mm, and a cost of 43 yuan / ton of steel; the steel billet underwent 0.6 mm of peeling, requiring two passes, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 43 + 25 * 2 = 93 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0175] Comparative Example 20: ZT005 coating was used, with 60% of the main component being ≥200 mesh, a coating thickness of 0.3 mm, and a cost of 42 yuan / ton of steel; the steel billet underwent 0.6 mm of peeling, requiring two passes, at a cost of 25 yuan / ton of steel. Total cost = coating cost + peeling cost = 42 + 25 * 2 = 92 yuan / ton of steel (decarburization depth of hot-rolled billet was 0).

[0176] Detailed cost comparison, for example Figure 2 As shown.

[0177] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A low-cost, zero-decarburization hot-rolled steel billet production process, characterized in that, Includes the following steps: (1) Apply anti-decarburization coating to the surface of the continuously cast billet; (2) The continuously cast billet is rolled to obtain a hot-rolled billet; (3) Finishing of hot-rolled billets; (4) Hot-rolled billet rolling; The decarburization prevention coating comprises the following components by mass percentage: quartz sand: 55%~65%, silicon carbide: 5%~8%, corundum: 10%~15%, zirconium corundum: 5%~8%, chromium oxide: 1%~3%, zirconium silicide: 1%~2%, barium borate: 1%~2%, and the remainder being phenolic resin binder; wherein, the proportion of quartz sand, silicon carbide, corundum, zirconium corundum, chromium oxide, zirconium silicide, and barium borate with a particle size ≥200 mesh is 55%~65%.

2. The low-cost, zero-decarburization hot-rolled steel billet production process according to claim 1, characterized in that, The thickness of the anti-decarburization coating in step (1) is 0.25mm~0.35mm.

3. The low-cost, zero-decarburization hot-rolled steel billet production process according to claim 1, characterized in that, The continuous casting billet mentioned in step (1) is a 60Si2MnA steel continuous casting billet, and the mass percentage of each component is as follows: C: 0.56%~0.64%, Si: 1.5%~2.0%, Mn: 0.7%~1.0%, P: ≤0.025%, S: ≤0.030%, Cr: ≤0.35%, and the remainder is Fe and unavoidable impurities.

4. The low-cost, zero-decarburization hot-rolled steel billet production process according to claim 1, characterized in that, The billet-making process in step (2) includes heating and rolling of the continuously cast billet. The heating process includes a preheating section, a second preheating section, a first heating section, a second heating section, a soaking section, and the first rolling. The temperature of the preheating section is ≤700℃, the temperature of the second preheating section is 900℃~1050℃, the temperature of the first heating section is 1180℃~1250℃, the temperature of the second heating section is 1210℃~1250℃, the temperature of the soaking section is 1210℃~1250℃, and the first rolling temperature is 1050℃~1160℃.

5. The low-cost, zero-decarburization hot-rolled steel billet production process according to claim 1, characterized in that, The finishing depth in step (3) is 0.6 mm.

6. The low-cost, zero-decarburization hot-rolled steel billet production process according to claim 1, characterized in that, The rolling process in step (4) includes heating and rolling of hot-rolled billets; wherein, the heating process of hot-rolled billets includes heating section 1, heating section 2, soaking section, and rolling start; the temperature of heating section 1 is 700℃~760℃, the temperature of heating section 2 is 930℃~980℃, the temperature of soaking section is 1050℃~1100℃, and the rolling start temperature is 940℃~1000℃.

Citation Information

Patent Citations

  • Anti-decarburization protective coating in spring steel billet heating process, and application thereof

    CN111607257A

  • Spring steel wire rod and production method thereof

    CN115074604A

  • Steel high-temperature anti-oxidation composite coating and preparation method thereof

    CN108047777A

  • Anti-decarburization separant

    CN114045053A